Ecophysiological Studies on Ageratum Conyzoides L. In South-West Nigeria - Sharma, B M (Annals of Arid Zone, 2016)
Ageratum conyzoides L. common annual herbaceous weed of croplands and wastelands in the warm regions of the world, was investigated under various ecophysiological conditions in Ibadan on an area of 1032 hectares during 1985-86 on three sites I-levelled area, II-elevated area, and III-the area in the vicinity of a lake. The plants in site II were comparatively taller but leaf number and biomass was more at site III. Phytosociological studies revealed Tridax-Ageratum-Synedrella community. The generic coefficient and diversity index were maximum for site I, maturity index for site II and species richness index for site III. Index of similarity was high for site II and site III. The soils were loamy sand with highest porosity at site II and highest field capacity at site III. Foliar calcium was higher at the pre-flowering stage. Crude protein in leaves ranged from 2.2 to 6.5% and was higher at the post-flowering stage. Tolerance to the water stress showed a significant difference in growth parameters. The transpiration rate was 4.2 mg/cm2/hr. The average seed number in an individual plant was 13897Â± 1610. The seeds showed a better germination in continuous light, when placed at the surface soil, and after storage for a longer duration.